Womb Outsourcing. Issue 5 (September 2015) - Frankford, David M.; Bennington, Linda K.; Ryan, Jane Greene
<x xml:space="preserve">Abstract</x> ABSTRACT Infertility affects more than 7 million American couples. As traditional treatments fail and the costs of hiring a surrogate increase in the United States, transnational commercial surrogacy becomes a feasible alternative for many couples. Infertile couples may opt for this choice after reading enticing Internet advertisements of global medical tourism offering "special deals" on commercial surrogacy. This is particularly true in India where couples from the United States can purchase transnational surrogacy for less than one-half or even one-third of the costs in the United States, including the cost of travel. The majority of surrogate mothers in India come from impoverished, poorly educated rural areas of India. Commercial surrogacy offers the lure of earning the equivalent of 5 years of family income. This multidisciplinary review of the literature suggests that the issue of commercial surrogacy is complex and influenced by a number of factors including expensive infertility costs, ease of global travel, and the financial vulnerability of Indian commercial surrogate mothers and their families. Questions are being raised about decision making by the surrogate mother particularly as influenced by gender inequities, power differentials, and inadequate legal protection for the surrogate mother. More research is needed to understand commercial surrogacy, especially research inclusive of the viewpoints of the Indian mothers and their families involved in these transactions.